Enable contrast version

# Tutor profile: Manasa S.

Inactive
Manasa S.
Assistant Professor in engineering college for 8 years
Tutor Satisfaction Guarantee

## Questions

### Subject:Basic Math

TutorMe
Question:

.Solve the equation x^3 - 3x^2 = -2 exact and approximate answers.

Inactive
Manasa S.

Cubic Equation: An equation that contains cubic polynomials is called a cubic equation. The most general form of the cubic equation is x^3+px^2+qx+r=0, where p, q, and r are constants. Answer and Explanation: Consider the given equation x^3−3x^2=−2 We re-write the equation as x^3−3x^2+2=0 By inspection, we see that x=1 will satisfy the equation. Therefore, x=1 must be the root of the equation. So, we can write x^3−3x^2+2=(x−1)(x^2−2x−2) Now, using the quadratic formula for the quadratic equation (x^2−2x−2)=0, we get: x=2±√(−2)^2−4(1)(−2)/2=2±√4+8/2=2±√12/2=2±2√3/2=1±√3 Therefore, the roots of the equation are x=1,1 −√3 1 + √ 3 .

### Subject:Electrical Engineering

TutorMe
Question:

Two-alternators are running in parallel. If the driving force of both the alternators is changed, this will result in change is A. frequency B. back emf C. generated voltage D. all of the above

Inactive
Manasa S.

Option A frequency

### Subject:Algebra

TutorMe
Question:

Expand and simplify the algebraic expression (x + 3)(x - 3) - (-x - 9)

Inactive
Manasa S.

(x+3) (x-3) - (-x-9) = x^2 - 9 + x + 9= x^2 + x

## Contact tutor

Send a message explaining your
needs and Manasa will reply soon.
Contact Manasa